2-DOF vortex-induced vibration of rotating circular cylinder in shear flow. (1st April 2022) - Ding, Lin; Kong, Hao; Zou, Qunfeng; Wang, Junlei; Zhang, Li
Abstract: The vortex-induced vibration (VIV) of a rigid cylinder which can rotate counterclockwise in a plane linear shear flow is numerically simulated within the range of reduced velocity 3≤ U*≤ 12. The rotating cylinder with two degrees of freedom (2-DOF) can vibrate freely in streamwise and cross-flow directions. The shear factors ( λ ) of the plane linear shear flow considered in this study are 0.05 and 0.1. The shear flow enhances the VIV of the 2-DOF rotating cylinder in two vibration directions. The maximum amplitude ratio of the rotating cylinder is 0.414 D in the streamwise direction and 0.820 D in the cross-flow direction. The amplitude ratio in the cross-flow direction ( A y / D ) rises significantly with the increase of the shear factor. The Magnus effect caused by rotation enlarges the offset from the initial position of the rotating cylinder. The movement trajectory of the non-rotating cylinder in the shear flow presents a droplet-shape, which is obviously different from the "8"-shaped trajectory of uniform flow. The droplet-shaped trajectory of a closed-loop indicates that the non-rotating cylinder under the action of shear flow has the same vibration frequency in the two vibration directions. Three vortex patterns of 2S, P+S, and U can be captured in the wake of the rotating circular cylinder. Highlights: Shear flow can enhance FIM of cylinder, especially non-rotating cylinder. Trajectory of non-rotating cylinder in shear flow is droplet shape. Vortex patterns of 2S, U, and P+S can be observed in the wake of cylinder in shear flow.